Cross-disciplinary knowledge: desperate call from business enterprises in coming smart working era - Lee, Jungwoo (Technological and Economic Development of Economy, 2014)
Science and technology is critical for execution and operations of modern businesses. As business operations consists of purposeful execution of technologies with appropriate social cooperation and coordination, knowledge in use is actually cross-disciplinary irrespective of domain or discipline of business. As information technology infiltrates today's businesses, people would need to work smarter using technologies including information technologies. This study explores executives’ perceptions of cross-disciplinary knowledge in coming era of smart businesses. An instrument was developed, asking questions about relative weights of different cross-disciplinary knowledge, frequencies and necessity of cross-disciplinary training, decision criteria in recruiting new employees and in promoting existing employees, and preferences in cross-disciplinary curriculum and sequence of relevant training courses. Results indicate that executives maintain high opinions concerning the value of science and technology as a critical contributor to the successful cross-disciplinary operation of their businesses. They seem to understand clearly that science and technology may not benefit their businesses unless it is applied in a cross-disciplinary manner. Executives prioritize cross-disciplinary knowledge domains as follows in order of importance: (1) Science Technology Enterprise (STE); (2) Science Technology Society (STS); and (3) Science Technology Humanities (STH). Implications are discussed with further research issues.